Gastroesophageal reflux disease: features in patients with metabolic syndrome - M. A. Livzan; E. A. Lyalyukova; I. V. Lapteva (Медицинский совет, 2014)
The article is a literature review of the major etiopathogenetic mechanisms and recent approaches to the treatment of gastroesophageal reflux disease in patients with metabolic syndrome. Recent data on the role of insulin resistance, impaired neurohumoral regulation of the upper gastrointestinal tract in patients with gastroesophageal reflux disease and metabolic syndrome is presented.